Advances in the pharmacological management of bacterial peritonitis. (13th August 2021) - Pörner, Daniel; Von Vietinghoff, Sibylle; Nattermann, Jacob; Strassburg, Christian P; Lutz, Philipp
ABSTRACT: Introduction: Bacterial peritonitis is an infection with high mortality if not treated immediately. In the absence of an intraabdominal source of infection, bacterial peritonitis may arise in patients with liver cirrhosis, in patients on peritoneal dialysis (PD) for end-stage renal disease or in patients with tuberculosis. In patients with cirrhosis, bacterial peritonitis may trigger acute on chronic liver failure with substantial mortality despite optimal treatment. In patients on PD, peritonitis may make continuation of PD impossible, necessitating the switch to hemodialysis. Areas covered: Recovery from peritonitis and prevention of complications depend on timely pharmacological management. Challenges are the broad microbiological spectrum with growing rates of antimicrobial resistance, the underlying chronic liver or kidney failure and high rates of relapse. The authors provide a review of predisposing conditions, diagnosis, and prevention of bacterial peritonitis with a particular focus on the pharmacological management. Expert opinion: Diagnosis of the type of bacterial peritonitis is essential to pharmacological management. In patients with spontaneous bacterial peritonitis, broad-spectrum antibiotics should be given intravenously in conjunction with albumin. In patients on PD, antibiotic therapy should be preferably applied intraperitoneally with empirical coverage of gram-positive and gram-negative bacteria. Secondary peritonitis usually requires surgical or interventional treatment.